SITEM INFORMASI GEOGRAFIS LOKASI PRAKTEK DOKTER SPESIALIS DAN APOTEK YANG DISARANKAN DI LAMONGAN DAN GRESIK BERBASIS ANDROID - Kemal Farouq Mauladi; Toni Muji Pangestu; Retno Wardhani (Universitas Islam Lamongan, 2017)
Geographic information systems (GIS) is a information system of processing and presention the data about the geographic condition into a range of accurate information. A specialist is a health worker who runs an important task in the Health, they are called specialists as because they in a specific area. Many people do not know the location of practices specialist, whether it is in Lamongan and Gresik, especially the people who live far from urban areas. With the problem, it is required system to inform the location of specialist practice and pharmacies in Gresik and Lamongan to facilitate good the people of the native or newcomers and wherever they are. In the development of this applications uses the Android operating system which is one of the most popular mobile phone operating system today, combined with the utilization of geographic information systems is certainly efficient for answering those questions. The utilization of Google Map API will certainly be very helpful in giving information on the location of the doctor and the pharmacies because the users can easily see the directions to the nearest way so it can be done more quickly, then the researcher makes the system with the title Geographic Information System Of Specialist Practice Location And The Pharmacies Suggested In Lamongan And Gresik Regency Based On Android.